Problems in Implementing the Project to Strengthen the Student Profile of Pancasila in the Perspective of Islamic Education - Pratiwi, Nur Vivi Yulianis; Haryanto, Budi (Hikmah, 2024)
The Pancasila Student Profile Strengthening Project aims to shape the character of students according to the values of Pancasila which are in harmony with Islamic teachings in building noble people. However, its implementation faces various problems. This research analyzes these problems at Tanggulangin Junior High School and Muhammadiyah Porong Junior High School with descriptive qualitative method, using observation, interview, and documentation. The research subjects consisted of principals, teachers, and students involved in the project activities. The results showed several obstacles, such as uneven student participation, limited teaching staff, lack of socialization, and financing issues. From an Islamic perspective, character building is in line with the concept of tarbiyah, which emphasizes morals, manners, and the integration of knowledge and faith. Islam emphasizes the importance of educators as role models (murabbi), Islamic environments, and learning methods that are in accordance with human nature. To make this project more effective, the integration of Islamic values in the education process needs to be strengthened in order to create insan kamil (complete human being). This research is expected to provide recommendations for schools in optimizing the implementation of the project to have a more positive impact on holistic student character building.